Premature small for gestational age infants fed an exclusive human milk-based diet achieve catch-up growth without metabolic consequences at 2 years of age. Issue 3 (13th November 2018) - Visuthranukul, Chonnikant; Abrams, Steven A; Hawthorne, Keli M; Hagan, Joseph L; Hair, Amy B
Abstract : Objective: To compare postdischarge growth, adiposity and metabolic outcomes of appropriate for gestational age (AGA) versus small for gestational age (SGA) premature infants fed an exclusive human milk (HM)-based diet in the neonatal intensive care unit. Design: Premature infants (birth weight ≤1250 g) fed an exclusive HM-based diet were examined at 12–15 months corrected gestational age (CGA) (visit 1) for anthropometrics, serum glucose and non-fasting insulin, and at 18–22 months CGA (visit 2) for body composition by dual-energy X-ray absorptiometry. Results: Of 51 children, 33 were AGA and 18 were SGA at birth. The SGA group had weight gain (g/day) equal to AGA group during the follow-up period. SGA had a significantly greater body mass index (BMI) z-score gain from visit 1 to visit 2 (0.25±1.10 vs −0.21±0.84, p=0.02) reflecting catch-up growth. There were no significant differences in total fat mass (FM) and trunk FM between groups. SGA had significantly lower insulin level (5.0±3.7 vs 17.3±15.1 µU/mL, p=0.02) and homeostatic model of assessment-insulin resistance (1.1±0.9 vs 4.3±4.1, p=0.02). Although regional trunk FM correlated with insulin levels in SGA (r=0.893, p=0.04), they had lower insulin level compared with AGA and no difference in adiposity. Conclusions: SGA premature infants who received an exclusive HM-based diet exhibited greater catch-up growth without increased adiposity or elevated insulin resistance compared with AGA at 2 years of age. An exclusive HM-based diet may improve long-term body composition and metabolic outcomes of premature infants with ≤1250 g birth weight, specifically SGA.